Выход водорода из никеля и палладия, стимулированный электронным пучком - Тюрин Ю. И. Юрий Иванович; Чернов И. П. Иван Петрович; Силкин В. М. Вячеслав Михайлович; Сыпченко В. С. Владимир Сергеевич; Хашхаш А. М. Адель Мохаммед; Никитенков Н. Н. Николай Николаевич; Толмачева Н. Д. Нелла Дмитриевна (2018, 2018)
Заглавие с экрана